Development of a New Technique for Measurement of Dielectric Properties of Oil Palm Fruits - You, Kok Yeow (2003)
The thesis describes the development of a low cost open-ended coaxial sensor for the determination of both complex permittivity and moisture content of the oil palm fruits of various degree of fruit ripeness. The sensor operating between 2 GHz and 4 GHz was fabricated from an inexpensive 4.1 mm outer diameter SMA coaxial stub contact panel and suitable for single fruit measurement. A theoretical analysis has been carried out to establish the optimum operating frequency based on the relation ship between the admittance and frequency of the sensor. The propagation of electromagnetic wave is assumed to be transverse electromagnetic (TEM) mode. The measurement system consists of the sensor and a PC-controlled vector network analyzer (VNA). A dielectric measurement software has been developed to control and acquire data from the VNA using Agilent VEE. The software is also used to calculate the complex permittivity from the measured reflection coefficient at each 201 frequency points between 2 GHz and 4 GHz. The permittivity values were then fitted to a dielectric mixture model to obtain the values of moisture content of oil palm fruits. The actual moisture content were found by standard oven drying method. A calibration equation relating the measured and predicted moisture content has been established based on more than 80 fruit samples. The equation was found to be accurate within 5.2 ± 0.4 % when tested on 69 different fruit samples. The values of moisture content obtained from the calibration equation were used in the mixture model to improve accuracy in the determination of the complex permittivity of the oil palm fruits. The sensitivities of the sensor in the measurement of the dielectric constant and loss factor of the oil palm fruits with respect to changes in moisture content were typically 0.82 and 0.05, respectively. The sensor can be used to monitor fruit ripeness based on the measurement of the magnitude of reflection coefficient alone. Fruits are considered to reach ripeness stage once the magnitude of the reflection coefficient is greater than 0.85 at optimum operating frequency 2.6 GHz.